Diseño de Agentes Antidiabéticos de Vanadio: Desarrollo y Avances Recientes - Alvino De la Sota, Nora (2007)
Design of Vanadium Antidiabetic Agents: Development and Recent AdvancesThe discovery of the enhanced hypoglycemic activity of bis(maltolate)oxovanadiu m (IV) (BMOV) compared to simplevanadium salts stimulated the design, synthesis and both in vitro and in vivo evaluation of a large variety of oxovanadium (IV)complexes with different organic ligands for their potential use as antidiabetic drugs that may be able to substitute, either partially or totally, the daily insulin injections used in the treatment of type 1 diabetes mellitus or the orally available hypoglycemic drugs usually used in combined therapy for type 2 diabetes.Recently, a close BMOV analogue, an ethyl substitute, has already successfully completed the phase 1 clinical trial in humans. The design of new types of complexes and the development of alternative delivery methods represent an active research field today.